Digital mental health treatment implementation playbook: successful practices from implementation experiences in American healthcare organizations - Mohr, David C.; Silverman, Alexandra L.; Youn, Soo Jeong; Areán, Patricia; Bertagnolli, Andrew; Carl, Jenna; Carlton, Tarolyn; Chaudhary, Neha; Cooper, David; DeVito, Shelly; Eaneff, Stephanie; Flom, Megan; et al. (Frontiers in Digital Health, 2025)
IntroductionDigital mental health treatments (DMHTs) have begun to be implemented in some healthcare systems across the United States. These implementations are conducted as business arrangements. Thus, information on successful or unsuccessful implementations is not published or disseminated. This slows progress, as experiences and learnings are siloed within each organization, hindering or preventing learning across implementations and slowing the progress. To address this, the Society for Digital Mental Health established a DMHT Implementation Workgroup, with the goal of developing a DMHT Playbook that describes current best practices in DMHT implementation in American healthcare settings.MethodsThe workgroup was comprised of representatives from 7 healthcare systems and 10 DMHT companies that have conducted implementations, along with other stakeholders and technical experts. The workgroup met virtually to discuss implementation of effective DMHT implementation processes and inform the development of an interview guide, which was then administered to another 20 key opinion leaders with DMHT implementation experience. Concepts and thematic constructs were extracted by experts in qualitative data analysis. These findings were discussed and refined by the Workgroup based on the Workgroup's experience.ResultsThe resulting playbook includes detailed methods, processes and procedures, representing practices that have been successful for implementing DMHTs in healthcare settings.DiscussionThe workgroup recognizes that DMHT implementation is a rapidly evolving field. The successful practices for DMHT implementation described in this playbook may be useful for improving the efficiency of future DMHT implementations in American healthcare systems. However, the authors caution that as the field rapidly evolves, successful implementation practices will likely evolve as well.